Sweet potato for Nutritional Security in Rainfed Plateau Ecosystem - Nath, Sujit K; Barik, K C; Sahoo, S K (Indian Farming, 2015)
Sweet potato, a low nutrient feeding crop was found suitable for plateau ecosystems of Odisha state. The changing climatic situation has warranted the food and nutritional insecurity in these areas. Sweet potato with less rainfall, giving a satisfactory yield of average 13.1 t per ha, helped in providing a sustainable security to the under privileged groups of the society.